2015
DOI: 10.4166/kjg.2015.66.4.209
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Cholecystectomy after Percutaneous Cholecystostomy for Acute Cholecystitis

Abstract: Background/Aims: Laparoscopic cholecystectomy is the standard treatment for acute cholecystitis. Percutaneous cholecystostomy is an alternative treatment to resolve acute inflammation in patients with severe comorbidities. The purpose of this study is to determine the optimal timing of laparoscopic cholecystectomy after percutaneous cholecystostomy for the patients with acute cholecystitis. Methods: This retrospective study was conducted in patients who underwent cholecystectomy after percutaneous cholecystost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 20 publications
0
26
1
Order By: Relevance
“…There are no randomized controlled trials on the best time for Lap‐C after PTGBD. Four observational studies featured various different times before surgery after PTGBD, and we assign these studies as evidence level C. Table provides a summary of these studies .…”
Section: Introductionmentioning
confidence: 99%
“…There are no randomized controlled trials on the best time for Lap‐C after PTGBD. Four observational studies featured various different times before surgery after PTGBD, and we assign these studies as evidence level C. Table provides a summary of these studies .…”
Section: Introductionmentioning
confidence: 99%
“…Our study was focused on the safety of the PC and the outcomes of critically ill patients after the procedure. According to numerous studies [8,16,20,24] PC can be used as a temporizing measure or as a definitive treatment option with a low number of delayed cholecystectomies [2]. Among 54 cases in our study, clinical status significantly improved and laparoscopic cholecystectomy was performed for 11 patients (20.37%).…”
Section: Discussionmentioning
confidence: 67%
“…Other studies introduce PC as a safe alternative treatment approach [22], especially useful when immediate cholecystectomy is unsafe [23]. There are several published studies comparing postoperative outcomes between early and late laparoscopic cholecystectomy following PC [24]. Jung et al reported no difference between groups in comorbid conditions that could affect surgical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the increased surgical risk due to aggressive surgery should also be prevented. For example, conservative surgery of acute gangrenous cholecystitis, such as percutaneous cholecystostomy[43,44], an alternative treatment for resolving acute inflammation, is theoretically suitable for patients in poor general condition, with a serious illness, unstable blood pressure during surgery, and other special circumstances. However, percutaneous cholecystostomy should be avoided for the reasons mentioned above.…”
Section: Discussionmentioning
confidence: 99%